PENGARUH PERSEPSI WAJIB PAJAK ORANG PRIBADI PADA PENERAPAN e-Filing TERHADAP TINGKAT KEPATUHAN FORMAL DALAM PENYAMPAIAN SPT TAHUNAN (Studi pada KPP Pratama Muara Bungo, KP2KP Muara Tebo, dan KP2KP Rimbo Bujang) - Eryasi Daryati; Muhammad Asman (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2019)
This study aims to determine the effect of ease of perception and perceived usefulness on the application of e-Filing both partially and simultaneously to the level of personal taxpayer's formal compliance in the submission of Annual Tax Returns at the KPP Pratama Muara Bungo, KP2KP Muara Tebo and KP2KP Rimbo Bujang. The test used in this study is the validity and reliability test for the research questionnaire, the classic assumption test, multiple regression test and hypothesis testing, this research test uses SPSS version 22 for windows. Based on the results of the distribution of 392 questionnaires there were 313 questionnaires that were filled in completely by the sample, and the results showed that partially the perception of ease and usefulness had an effect on the level of formal compliance in the submission of Annual Tax Returns with significant values ​​of t-count of 0,000 and 0.006 smaller than 0.05, while simultaneous perceptions of convenience and usefulness affect the level of formal compliance in the submission of Tax Returns with a significant value of F-count 0,000 smaller than 0.05.